Terror on Tuesday - Purser, Ann (New York : Berkley Prime Crime, 2004)
Working-class mum and housecleaner Lois Meade plies her sleuthing skills once again after discovering a dead body--dressed in a suit of armor--in a chapel.
89095
Keywords: Married women -- England -- Fiction; Police -- England -- Fiction; Cleaning personnel -- England -- Fiction; Private investigators -- England -- Fiction; Murder -- Investigation -- England -- Fiction; Detective and mystery stories